2021
DOI: 10.1093/ajhp/zxab390
|View full text |Cite
|
Sign up to set email alerts
|

An electronic tool for health systems to assess and communicate discharge medication access

Abstract: Disclaimer In an effort to expedite the publication of articles, AJHP is posting manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Once the discharge antibiotic selection, dose, and duration were agreed upon, the pharmacist entered the discharge order in the EHR per protocol, with an additional note on the appropriate end date, to be signed by the provider. The pharmacist could also send an electronic discharge medication cost inquiry to the discharge pharmacy queue to review medication coverage and copayments prior to placing the discharge order 32 . A note was then placed in the EHR by the pharmacist as a plan of care document, describing the discharge antimicrobial regimen and end date.…”
Section: Interventions and Pharmacist Role In Stewardship At Tocmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the discharge antibiotic selection, dose, and duration were agreed upon, the pharmacist entered the discharge order in the EHR per protocol, with an additional note on the appropriate end date, to be signed by the provider. The pharmacist could also send an electronic discharge medication cost inquiry to the discharge pharmacy queue to review medication coverage and copayments prior to placing the discharge order 32 . A note was then placed in the EHR by the pharmacist as a plan of care document, describing the discharge antimicrobial regimen and end date.…”
Section: Interventions and Pharmacist Role In Stewardship At Tocmentioning
confidence: 99%
“…The pharmacist could also send an electronic discharge medication cost inquiry to the discharge pharmacy queue to review medication coverage and copayments prior to placing the discharge order. 32 A note was then placed in the EHR by the pharmacist as a plan of care document, describing the discharge antimicrobial regimen and end date. Interprofessional communication was primarily pager-based.…”
Section: Health System Experience: Patient Identification and Pharmac...mentioning
confidence: 99%
“…Insurance prior authorizations (PAs) are a particular pain point for patients and providers and make up the most common post-discharge inquiry about prescriptions. 4 While intended to control healthcare cost without negatively impacting health outcomes, in practice, PAs introduce administrative burden to healthcare staff and lead to decreased medication usage. [5][6][7] Studies have shown that each PA takes a median of 30 to 46 minutes of providers' time to complete and 22 days to process.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing use of EHRs, interventions embedded within the EHR have shown potential to improve the discharge process on a systemic level. 4,22,23 At an 8-hospital system, a transition-in-care (TIC) team composed of pharmacists and nurses followed up with patients after discharge to identify and help resolve any postdischarge barriers. The recurrent issues identified by the TIC team from patients' responses prompted the creation of system-wide EHR interventions to address the most common barriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation